Geologi dan Potensi Batubara di Daerah Bonggo dan Sekitarnya Kabupaten Jayapura, Propinsi Papua - Marcelino N. Yonas (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2016)
Geographically, the study area is in the region and surrounding Bonggo, Jayapura Regency. Now adays, the energy needs requires a continuous exploration in energy commodities (oil and coal).Geologically, Jayapura Residence has considerable potential for coal commodity. The research itselfis located at coordinates 139025'51